Four new Dolichopoda species from Greece, one Troglophilus new to Greece and new locality records (Orthoptera, Rhaphidophoridae) - Sotiris Alexiou; Kostas Bakolitsas; Claudio Di Russo; Mauro Rampini (Contributions to Entomology)
We describe four new species of the genus Dolichopoda from various areas of Greece, namely D. athosensis sp. nov., D. dirussoi sp. nov., D. karoutsosi sp. nov. and D. kotsabasi sp. nov. New locality records for Greece for the genera Dolichopoda and Troglophylus are given, in addition to the presence of Troglophilus brevicauda as a new country record. We discuss the relationship with the already known species of the area.